VARIATION IN CHITINOID STRUCTURES OF HAMATOPEDUNCULARIA WALLAGONIUS N. SP. IN RELATION TO SEASON - SINGH, H.S.; AGRAWAL, SHILPI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Hamatopeduncularia wallagonius n.sp. infect gill filaments of Wallago attu. During the course of study of the population dynamics, seasonal periodicity and morphology of this parasite, it was noticed that there exists a clear cut variation in the size of chitinoid elements of the parasite in relation to season (summer & winter). Since sizes of chitinoid elements are the principal taxonomic characters (Ergens, 1965 & 1965). Therefore, it is necessary to consider the variations, in size of these elements while describing a new taxa, present paper deals with the changes marked in the chitinoid elements of this Parasite in relation to season.